Distribution of pituitary adenylate cyclase‐activating polypeptide (PACAP) in the human testis and in testicular germ cell tumors. (27th April 2013) - Nakamura, K.; Nakamachi, T.; Endo, K.; Ito, K.; Machida, T.; Oka, T.; Hori, M.; Ishizaka, K.; Shioda, S.
Summary Pituitary adenylate cyclase‐activating peptide (PACAP) is a neuropeptide expressed in the central nervous system and peripheral organs. Previous studies revealed the role and distribution of PACAP in the rodent testis, however, its presence in the human testis and in testicular germ cell tumors is not known. We used RT‐PCR and immunohistological observations to investigate whether human testicular tissue and testicular germ cell tumors contain PACAP. The mRNAs for PACAP and its receptors were detected in total RNA extracted from human testes. PACAP immunoreactivity was observed in spermatogonia and spermatids from normal testes. In contrast, diffuse PACAP immunopositivity was observed in seminoma tumor cells, while only faint immunoreactivity was observed in embryonal carcinoma cells. Our data suggest that PACAP may play a role in human spermatogenesis and in testicular germ cell tumor development.